The Effectiveness of English Ice Breaker Games to Increase the Student’s Motivation in Learning English at Politeknik Penerbangan Makassar - Ahmad Rossydi (International Journal of Advanced Science and Technology, 2020)
This study aims to analyze how effective leaning English by English ice breaker games for a cadet at Politeknik Penerbangan Makassar. Learning English at Politeknik Penerbangan Makassar had some problems such they don’t have any spirit to learn English and the ways of teaching at Politeknik Penerbangan Makassar is not interesting and make them get bored, so that’s why around 80% from 24 cadets they don’t have any motivation in learning English. It needed a strategy attract the cadets in learning English, one of them is using ice breaker games. Through ice breaker games, it is expected to facilitate the cadets an effective distance learning process and attract the cadets in learning English. This research is a qualitative research. The procedure for primary data collection is done by in-depth interviews with cadets and English lecturers. Based on the results of an online questionnaire given to 24 respondents taken from the first grade stated that 83% of respondents stated that they have high motivation in learning English using ice breaker games, 13% of respondents have low motivation, 3% of respondents they don’t have any motivation to learn English by using ice breaker games. By using ice breaker games strategy, it can support the cadet’s motivation in learning English. English ice breaker games is effective used for cadets to improve their English skills and provide benefits for cadets in understanding English material.